CRITIQUES OF MINIMAL REALISM - Park, Seungbae (Problemos, 2017)
Saatsi’s minimal realism holds that science makes theoretical progress. It is designed to get around the pessimistic induction, to fall between scientific realism and instrumentalism, and to explain the success of scientific theories. I raise the following two objections to it. First, it is not clear whether minimal realism lies between realism and instrumentalism, given that minimal realism does not entail instrumentalism. Second, it is not clear whether minimal realism can explain the success of scientific theories, given that it is doubtful that theoretical progress makes success likely. In addition to raising these two objections, I develop and criticize a new position that truly falls between realism and instrumentalism.